Programmable Periodicity of Quantum Dot Arrays with DNA Origami Nanotubes - Bui, Hieu (American Chemical Society, 2010)
[Image: see text] To fabricate quantum dot arrays with programmable periodicity, functionalized DNA origami nanotubes were developed. Selected DNA staple strands were biotin-labeled to form periodic binding sites for streptavidin-conjugated quantum dots. Successful formation of arrays with periods of 43 and 71 nm demonstrates precise, programmable, large-scale nanoparticle patterning; however, limitations in array periodicity were also observed. Statistical analysis of AFM images revealed evidence for steric hindrance or site bridging that limited the minimum array periodicity.